2019
DOI: 10.1139/cjes-2017-0244
|View full text |Cite
|
Sign up to set email alerts
|

Provenance analysis of the Dezadeash Formation (Jurassic–Cretaceous), Yukon, Canada: implications regarding a linkage between the Wrangellia composite terrane and the western margin of Laurasia

Abstract: The Mesozoic convergence of the allochthonous Wrangellia composite terrane (WCT) with the western margin of Laurasia coincided with the construction of the Chitina magmatic arc on the WCT, and the dispersal of volcanic flows and sediment gravity flows into an adjacent flysch basin. The basin, preserved as the Gravina–Nutzotin belt, includes the Dezadeash Formation in southwest Yukon, the Nutzotin Mountains sequence in southern Alaska, and the Gravina belt in southeastern Alaska. The Dezadeash Formation is a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 102 publications
1
34
0
Order By: Relevance
“…Detrital zircon geochronological data for sandstone samples from the Kahiltna assemblage have been published from the central Alaska Range (Hampton et al, 2007(Hampton et al, , 2010 and from the western Alaska Range (Kalbas et al, 2007;Bradley et al, 2009;Hults et al, 2013). Similar analyses have also been published for the Nutzotin basin (Hults et al, 2013), the Dezadeash basin (Lowey, 2019) and the adjacent Kluane schist (Israel et al, 2011), and for Gravina basin strata (Yokelson et al, 2015, and references therein). All these studies identified a distinct contrast in detrital zircon populations A B Structure section line (Fig.…”
Section: ■ Previous Workmentioning
confidence: 82%
See 2 more Smart Citations
“…Detrital zircon geochronological data for sandstone samples from the Kahiltna assemblage have been published from the central Alaska Range (Hampton et al, 2007(Hampton et al, , 2010 and from the western Alaska Range (Kalbas et al, 2007;Bradley et al, 2009;Hults et al, 2013). Similar analyses have also been published for the Nutzotin basin (Hults et al, 2013), the Dezadeash basin (Lowey, 2019) and the adjacent Kluane schist (Israel et al, 2011), and for Gravina basin strata (Yokelson et al, 2015, and references therein). All these studies identified a distinct contrast in detrital zircon populations A B Structure section line (Fig.…”
Section: ■ Previous Workmentioning
confidence: 82%
“…Trimble samples generally have 0%-5% Precambrian grains, and no samples have a statistically significant Precambrian age population. The Late Jurassic age populations are correlative with volcanic and plutonic rock ages within the "Chitina arc" sequence of the Alexander-Wrangellia-Peninsular terrane from the Wrangell Mountains down into southeastern Alaska (Plafker et al, 1989;Trop and Ridgway, 2007;Beranek et al, 2017;Lowey, 2019). The Early Jurassic ages are well represented in both intermediate volcanic and felsic plutonic rocks within the Alexander-Wrangellia-Peninsular terrane ("Alexander-Wrangellia-Peninsular igneous" in Fig.…”
Section: Detrital Sources Of the Petrofacies Units Of The Southeastermentioning
confidence: 85%
See 1 more Smart Citation
“…Nutzotin Mountains strata are locally in depositional contact with the Wrangellia-Alexander terrane and in other areas have been thrust southward (present-day coordinates) over Wrangellia along south-verging thrust faults (Richter, 1976;Manuszak et al, 2007). Sedimentological and detrital data from the Nutzotin Mountains sequence and Dezadeash Formation reflect a provenance from sources within the Wrangellia-Alexander terrane (Manuszak et al, 2007;Lowey, 2011;Fasulo et al, 2018;Lowey, 2018), similar to the southern Kahiltna assemblage. Manuszak et al (2007) infer that the Nutzotin strata accumulated in a compressional basin setting linked to Late Jurassic-Early Cretaceous shortening, uplift, and unconformity development documented in the Wrangellia composite terrane south of the Nutzotin basin (Trop et al, 2002).…”
Section: ■ Tectonic Synthesis: Evolution Of the Alaska Range Suture Zonementioning
confidence: 91%
“…The absence of detrital zircon ages from the regionally extensive Late Cretaceous arc rocks in the Jurassic‐Cretaceous basins in eastern Alaska (Figures D and E) and southeastern Alaska (Figures G and H) suggest that deposition may have ended earlier in these basins relative to the basins in south‐central Alaska. As part of the Jurassic‐Cretaceous basins, the Dezadeash Formation within the Dezadeash basin in Yukon, Canada also shows an absence of Late Cretaceous detrital zircon ages (Lowey, ). Lowey () presents new U‐Pb analyses of detrital zircons from the Dezadeash Formation that range from ~2111–145 Ma, with Mesozoic ages as the most abundant and a youngest dominant peak age at ~157 Ma (Figure A in Lowey, ).…”
Section: Discussionmentioning
confidence: 99%